Students’ Perceptions on Increased Pronunciation Ability By Using “Coco” Film At SMP N 1 Kombi - Y. Languju, Endriko; Liando, Nihta V.F; Rorimpandey, Rinny (Program Studi Pendidikan Bahasa Inggris, 2024)
Language is a system of symbols that are meaningful and articulate sound (generated by said tool) which are arbitrary and conventional, which is used as a means of communicating by a group of human beings to give birth to feelings and thoughts, Wibowo (2001:3). Language is a system of express and report what happens on the nervous system, Pengabean (1981:5). Providing two language understanding. this research the researcher used questionnaire to gather perceptions from students about the use of film .The results elicit a favorable response from the students, with over half of them expressing agreement with each given assertion. However, inside each statement, there are certain phrases that serve as evaluations for teachers, including the choice of films, which should be a priority for teachers in schools. An appropriate film selection will facilitate the students' comprehension of vocabulary, pronunciation, and structural elements within the movie. Firstly, students often view watching films as an enjoyable and engaging activity. Unlike traditional pronunciation drills, which can feel monotonous and repetitive, films provide an immersive experience that captivates students' attention. When students are engaged and interested, they are more likely to pay attention to the pronunciation of words and phrases spoken by native speakers in the film. This increased exposure to authentic language usage can help students develop a more natural and accurate pronunciation